Pengaruh Latihan Combination Play terhadap Kolektivitas Tim Futsal Putra UNJ - Wijdan Fagan Radinka; Andri Irawan; Dadan Resmana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
In this problem, the State University futsal team The Jakarta State University futsal team has a problem of lack of success in attacking and controlling the ball through the application of ineffective combination play, which hinders the ability of the Jakarta State University team to create space to become opportunities and create goals. One of the problems that may arise is the lack of variety in the combination play of players when attacking and controlling the ball. The research method used in this research is the experimental method. The variables studied, including the independent variable and the dependent variable, have been determined explicitly by the researcher since the beginning of the study. The independent variable in this study is combination play training, while the dependent variable is collectivity. The results showed that there was an increase in collectivity ability after being given combination play training with a tcount value of 6.23 which is greater than ttable 2.16 with a significance level of 0.05. This is in accordance with the framework and theory as well as the research hypothesis which says that there is an effect of combination play training on futsal collectivity. Based on the problems found, which are supported by literature review, framework and research results, it can be concluded that there is an effect of combination play training on the collectivity of the UNJ futsal team.